REPRESENTATION OF CAPITALISM AND MATERIALISM IN JESSIE J’S PRICE TAG: A MARXIST PERSPECTIVE - Silvia Fara Diba Siregar; Rahma Amalia; Elva Gracia Sidabutar; Erluna Elekta Rajagukguk; T.Thyrhaya Zein (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This research seeks to examine how capitalism and materialism are represented in the lyrics of Jessie J’s song Price Tag from a Marxist point of view. The study centers on the portrayal of money domination as a manifestation of capitalist practice and on materialism as an element of commodification in contemporary society. The research applies a qualitative method using a descriptive-interpretative approach. The data consist of words, phrases, and sentences taken from the lyrics of Price Tag and are interpreted through Marxist literary criticism. Data were collected through documentation and library research, while the analysis followed the Miles, Huberman, and Saldana model, covering data condensation, data presentation, and conclusion drawing. The findings indicate that Price Tag expresses criticism of the power of money and the culture of materialism within capitalist society. The lyrics illustrate how capitalism forms social consciousness, causing money and consumption to become dominant standards for measuring happiness and social status. The song also reveals commodification, a process that changes social relationships into economic relations grounded in exchange value. Through comparison, this research shows that Price Tag differs from many contemporary popular songs that tend to glorify luxury and materialistic lifestyles. Through cause-and-effect analysis, the study also demonstrates that capitalism encourages consumerist habits, artificial needs, and social alienation. Therefore, this study confirms that song lyrics can operate as a medium of social criticism against capitalist ideology in modern popular culture. Keywords: Capitalism; Materialism; Marxism; Song lyrics; Social criticism